Implementasi Sistem Monitoring Suhu dan pH Berbasis Internet of Things (IoT) pada Budidaya Ikan Nila Gesit (Oreochromis niloticus) dengan Bioflok - Noor Avia Camelia; Muhammaad Taufiq; Hani Rubiani (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The biofloc system has become an innovative aquaculture method due to its ability to maintain water quality and improve fish growth. The implementation of the Internet of Things (IoT) enables real-time monitoring of water quality parameters, particularly temperature and pH, which are essential for supporting fish cultivation. This study aimed to implement an IoT-based monitoring system to observe water temperature and pH conditions in a biofloc system and to analyze their relationship with the Specific Growth Rate (SGR) of Gesit tilapia (Oreochromis niloticus). This research employed a quantitative approach using an experimental method involving two biofloc ponds with different stocking densities of 1,000 and 900 fish. Temperature, pH, and fish growth data were collected over a 60-day cultivation period and analyzed using descriptive statistical methods. The results showed that water temperature ranged from 25.1°C to 28.0°C, while pH ranged from 6.5 to 7.9, indicating that both parameters remained within the optimal range for tilapia cultivation. The SGR value of the pond stocked with 900 fish reached 1.96% per day, which was higher than the pond stocked with 1,000 fish at 1.80% per day. These findings demonstrate that the IoT-based monitoring system effectively supports continuous water quality monitoring and that a stocking density of 900 fish provides better growth performance in a biofloc cultivation system.